Representasi Nilai-Nilai Pendidikan Karakter dalam Cerpen “Gus Jakfar” Karya KH A. Mustofa Bisri: Kajian Sosiologi Sastra - Sani, Rizky Mutiara; Septiana, Hespi (Universitas Muhammadiyah Surabaya, 2025)
This research focuses on finding the values ​​of character education in the short story entitled “Gus Jakfar” by KH A. Mustofa Bisri through a sociological study of literature. The use of sociological literary studies is intended to analyze social interactions in short stories which produce exemplary values ​​in the form of character education. The method used is descriptive qualitative (QD) with data collection techniques using library research, where data is obtained from literature in the form of short stories, articles and books. Next, the data was analyzed using the Miles and Huberman technique through three stages, namely